A BAP31 intrabody induces gastric cancer cell death by inhibiting p27kip1 proteasome degradation. Issue 8 (17th January 2019) - Chen, Jing; Guo, Haotian; Jiang, Haitao; Namusamba, Mwichie; Wang, Changli; Lan, Tian; Wang, Tianyi; Wang, Bing
Abstract : B‐cell receptor‐associated protein 31 (BAP31) is a ubiquitously expressed endoplasmic reticulum (ER) membrane protein that has been found to be overexpressed in gastric intestinal‐type adenocarcinoma. We first studied the relationship of BAP31 with 84 kinds of tumor‐associated antigens and found that BAP31 can specifically interact with and regulate the proteasome degradation of the cyclin kinase inhibitor p27 kip1, which is one of the most frequently dysregulated tumor suppressor proteins in human cancers. Therefore, we screened antibodies against BAP31 from a human VH single‐domain antibody library and expressed the antibodies intracellularly. It was found that one of the intrabodies (VH‐D1) specifically inhibited p27 kip1 proteasome degradation, possibly by blocking the combination of BAP31 with p27 kip1 . VH‐D1 displayed therapeutic effects, as it was able to reduce the growth of human gastric cancer (GC) cell xenografts in nude mice. This effect was due to inhibition of the proliferation and subsequent activation of caspase‐dependent apoptosis. Thus, BAP31 is a potential target for the suppression of GC via an intrabody‐based approach. Abstract : What's new? B‐cell receptor‐associated protein 31 (BAP31), an endoplasmic reticulum membrane protein, is highly expressed in gastric intestinal‐type adenocarcinoma, a rare form of gastric cancer (GC). Little is known, however, about the relevance of BAP31 expression in this tumor type. Here, overexpression of BAP31 in GC cells was associated with decreased protein levels of the cyclin kinase inhibitor p27kip1. In mechanistic studies, BAP31 was found to regulate p27kip1 via proteasome degradation. VH‐D1, a human immunoglobulin heavy chain (VH) single‐domain antibody acting against BAP31, blocked p27kip1 degradation, leading to growth inhibition and apoptotic death in GC cells and GC tumors in mice.